Infective endocarditis: a consumptive disease among the elderly - Vilma Takayasu; Fabiana Roberto Lima; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2011)
The clinical presentation of infective endocarditis varies according to the etiologic agent and the host. In elderly individuals, infective endocarditis can be difficult to diagnose and poses a challenge for the physician. The course of subacute infective endocarditis is indolent, and the onset of cardiac structural lesion is slow and gradual. In elderly patients, anemia and weight loss are occasionally the only or the most striking symptoms. In such cases, the clinical reasoning process leads to a hypothesis of wasting syndrome or neoplastic disease, especially when there is no fever. We report the case of an elderly patient who had mitral insufficiency due to degenerative valve disease and presented with bacterial endocarditis due to Streptococcus mitis. The patient was not treated, because the diagnosis was not established in a timely manner. It is of note that the patient presented with marked weight loss and no fever. The autopsy revealed impairment of the mitral valve and left atrium due to endocarditis, as well as lung involvement due to chronic inhalation of smoke from biomass burning, such as that produced by wood-burning stoves.